Kegiatan Ekstrakurikuler Sanggar Konsultasi Remaja (SKR) di Sekolah Menengah Atas Negeri 7 Padang - Weldiana, Weldiana; Daharnis, Daharnis; Mudjiran, Mudjiran (Konselor, 2012)
The purpose of Teen Consultation Center (TSC) extracurricular is to develop students’ ability become youth counselor. The purpose of this research is to describe TSC extracurricular activity at SMA N 7 Padang based on the students’ opinion about the development TSC by counseling teacher and TSC implementation by youth counselor. This research can be categorized quantitative approach, descriptive research. Research finding explains students’ opinion about TSC development by counseling teacher is good and TCR implementation has been done.